Perioperative management of emergency and elective surgeries during the pandemic. Issue 1 (1st January 2023) - Boike, Sydney; Mir, Mikael; Olson, Holly; Cole, Delaney; Rauf, Ibtisam; Surani, Salim; Khan, Syed Anjum
ABSTRACT: The effects of the 2019 novel coronavirus, SARS-CoV-2, and its associated pandemic are complex and widespread. It has permeated all aspects of daily life around the world. Unsurprisingly, it also had significant impacts on proceedings within hospitals around the world as well. Most notably, the multiple waves of the pandemic have each had untoward effects on surgical productivity within hospital systems. More specifically, the disruption of surgical procedures has impacted both emergent and elective cases. In the context of emergent procedures, hospital systems have had to reevaluate how they define 'emergent, ' forcing them to determine which cases could not be rescheduled versus those that could. Elective procedures, on the other hand, were nearly halted altogether in the initial pandemic waves. If these were not completely stopped in some places, then they were greatly reduced. This paper will serve to describe the effect the pandemic has had on the proceedings of both elective and emergent surgeries. It will also describe how we have reevaluated and changed the way we define 'emergent' surgeries and describe the potential implications of this. We will also describe literature that speaks to the implications of the delay of elective procedures. Additionally, the cost implications of fewer surgical procedures performed will be discussed. Finally, we will describe literature that has established protocols for scheduling surgeries in waves of the pandemic, how these have evolved over time, and how they have created confusion for hospital systems navigating the pandemic.